2021
DOI: 10.1183/13993003.00266-2021
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of contact investigation among contacts of tuberculosis patients: a systematic review and meta-analysis

Abstract: BackgroundWe aimed to evaluate the effectiveness of contact investigation in comparison to passive case-detection alone and estimated the yield of co-prevalent and incident tuberculosis (TB), and latent tuberculosis infection (LTBI) among contacts of patients with TB.MethodsA systematic search was undertaken of studies published between January 1, 2011 and October 1, 2019 in the English language. The proportion of contacts diagnosed with co-prevalent TB, incident TB and/or LTBI was estimated. Evaluation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
4
26
1
1
Order By: Relevance
“…A recent systematic review suggested that the pooled prevalence of TB in close contacts was 3•6% (95% CI: 3•3-4•0), and that contact investigation could increase TB case notification and thereby decrease the incidence of TB in the population. 18 In developed countries, index cases have been found to have 6-12 close contacts [19][20][21][22] who could potentially constitute 10-20% 23,24 of the total TB burden. Accordingly, the WHO strongly recommends systematic screening for TB disease among close contacts.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review suggested that the pooled prevalence of TB in close contacts was 3•6% (95% CI: 3•3-4•0), and that contact investigation could increase TB case notification and thereby decrease the incidence of TB in the population. 18 In developed countries, index cases have been found to have 6-12 close contacts [19][20][21][22] who could potentially constitute 10-20% 23,24 of the total TB burden. Accordingly, the WHO strongly recommends systematic screening for TB disease among close contacts.…”
Section: Discussionmentioning
confidence: 99%
“…TST or IGRA positivity in this population is estimated to be 50•5%. 6 Of the remaining 49•5% of household contacts, an estimated 44% (254/576) remain persistently TST-negative or IGRA-negative. 7 83% of these individuals who are TST-negative or IGRA-negative were consistently negative on extended evaluation, 8 providing an estimated 20% prevalence of resistance.…”
Section: Authors' Replymentioning
confidence: 99%
“…Systematic reviews that have assessed the prevalence of TB disease among contacts have consistently reported an increased risk of developing active TB disease in child contacts < 5 years of age. In addition, a meta-analysis of individual randomized trials demonstrated that contact investigation increased TB case notification (RR 2.5 [95% CI: 2.0-3.2]), and decreased mortality (RR 0.6 [95% CI: 0.4-0.8]) [5]. Despite supportive evidence and existing WHO and national-level recommendations for CCM, many barriers still exist to their implementation.…”
Section: National Policies and The Policy-practice Gapmentioning
confidence: 99%